If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24x+6-26x=3-5
We move all terms to the left:
24x+6-26x-(3-5)=0
We add all the numbers together, and all the variables
24x-26x+6-(-2)=0
We add all the numbers together, and all the variables
-2x+8=0
We move all terms containing x to the left, all other terms to the right
-2x=-8
x=-8/-2
x=+4
| 4u-4=-32 | | 3x2-20=2x2-x | | 8x+26=5(x-7) | | -12=-2x-x | | 7(x-9)-10=50 | | 14+5=-5x+-6(-3x+15)+5 | | -2=-k-k | | 12(12+x)=576 | | 6w-13w=-21 | | 4(8b+1)=4+5b | | 18-5x=30-7x | | -4-8(1-5d)=17 | | 6n+4+6=-8 | | 3x=6-3(x+4) | | 2(3x+7)+4x=9x-3 | | 4x+4=39 | | 25x=2.5 | | 9x+7-3x=10x-53 | | z/3+5=3 | | 1/4x+2=x-5 | | x^+10x+12=36 | | -11x+9=3(6x+3) | | 3a-6=27 | | 4x-2x+8=16+2+10 | | 8x-9=-2+41 | | 2.85-7=12.85a-2 | | 4x+1/3=19 | | 60=x*(x+4 | | 2x+(x+200)=2480 | | 8x+7=3`1 | | 3x+4/2=9,5 | | 3x=(x+42)=90 |